HBR's 10 must reads for new managers. - Hill, Linda A. (Linda Annette), 1956-; Watkins, Michael, 1956-; Walker, Carol A.; Reid, Erin.; Cialdini, Robert B.; Goleman, Daniel; Ibarra, Herminia, 1961-; Gabarro, John J.; Ibarra, Herminia, 1961-; Oncken, William; Watkins, Michael, 1956-; Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2017)
"Develop the mindset and presence to successfully manage others for the first time. If you read nothing else on becoming a new manager, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you transition from being an outstanding individual contributor to a great manager of others. This book will inspire you to: develop your emotional intelligence; influence your colleagues with the science of persuasion; assess your team and enhance its performance; network effectively to achieve business goals and for personal advancement; navigate relationships with employees, bosses, and peers; get support from above; view the big picture in your decision-making * balance your team's work and personal life in a high-intensity workplace."--Publisher description.
Becoming the boss / by Linda A. Hill -- Leading the team you inherit / by Michael D. Watkins -- Saving your rookie managers from themselves / by Carol A. Walker -- Managing the high-intensity workplace / by Erin Reid and Lakshmi Ramarajan -- Harnessing the science of persuasion / by Robert B. Cialdini -- What makes a leader / by Daniel Goleman -- The authenticity paradox / by Herminia Ibarra -- Managing your boss / by John J. Gabarro and John P. Kotter -- How leaders create and use networks / by Herminia Ibarra and Mark Lee Hunter -- Management time: who's got the monkey? / by William Oncken, Jr., and Donald L. Wass -- Bonus article: How managers become leaders / by Michael D. Watkins.
Includes index.
Includes bibliographical references and index.
Print version record.
OCLC control number change
Keywords: Management; Leadership; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Leadership; Management; elektronické knihy; electronic books